Mice Expressing Mutant Trpv4 Recapitulate the Human TRPV4 Disorders. (August 2014) - Weinstein, Michael M; Tompson, Stuart W; Chen, Yuqing; Lee, Brendan; Cohn, Daniel H
ABSTRACT Activating mutations in transient receptor potential vanilloid family member 4 (Trpv4) are known to cause a spectrum of skeletal dysplasias ranging from autosomal dominant brachyolmia to lethal metatropic dysplasia. To develop an animal model of these disorders, we created transgenic mice expressing either wild‐type or mutant TRPV4. Mice transgenic for wild‐type Trpv4 showed no morphological changes at embryonic day 16.5 but did have a delay in bone mineralization. Overexpression of a mutant TRPV4 caused a lethal skeletal dysplasia that phenocopied many abnormalities associated with metatropic dysplasia in humans, including dumbbell‐shaped long bones, a small ribcage, abnormalities in the autopod, and abnormal ossification in the vertebrae. The difference in phenotype between embryos transgenic for wild‐type or mutant Trpv4 demonstrates that an increased amount of wild‐type protein can be tolerated and that an activating mutation of this protein is required to produce a skeletal dysplasia phenotype. © 2014 American Society for Bone and Mineral Research